0077 Objective Sleep and Neural Response to Thermal Pain Testing Following Cognitive Behavioral Treatment in Patients with Comorbid Insomnia and Fibromyalgia: A Pilot Study. (27th May 2020) - McCrae, C; Craggs, J; Curtis, A; Staud, R; Berry, R; Robinson, M
Abstract: Introduction: Fibromyalgia (FM) is characterized by high rates of insomnia and abnormal central pain processing/heightened response to stimuli (i.e., central sensitization). This study examines whether cognitive behavioral treatments (CBTs) that target insomnia and pain improve central pain processing [indicated by decreased response to quantitative sensory testing (QST) using thermal stimuli] in patients with fibromyalgia and insomnia. Methods: Before and after CBT-I, CBT-P or waitlist, adults (N=32, Mage =55.9, SD=12.2) with FM and insomnia completed QST during f MRI (Phillips Achieva 3T scanner), 14-daily pain ratings [least(0)-most(100) intense pain imaginable] and 1-night in-home polysomnography (AURA/Grass Technologies). Imaging data were processed using Brain Voyager (Brain Innovation/Netherlands). Random effects ANCOVA identified regions with significant group (3-CBT-I, CBT-P, waitlist) by time (baseline, post-treatment) interactions in brain hemodynamic response to QST. Linear regressions (using residualized change scores) were conducted for each significant region to examine how pain and sleep changes (%Stages 1–3 NREM, %REM) were related to brain response changes. Results: Eleven regions exhibited significant interactions (ps&lt.00; large effects; right hemisphere: inferior frontal, superior temporal, mid-occipital, and cingulate gyri, lentiform nucleus; left hemisphere: angular, superior temporal, mid-frontal, inferior occipital, mid-temporal, and inferior frontal gyri). CBT-I decreased brain response to QST in 8 regions and CBT-P in 3 regions (CBT-I effects&gtCBT-P). Waitlist increased response in 6 regions. Pain ratings, %Stage 2 and %REM sleep were not significant for any region and were dropped from the models. Increased %Stage 1 and/or %Stage 3 predicted decreased brain response to QST in 8 of the 11 regions (ps&lt.01), accounting for 19–45% of the variance. Conclusion: Compared to CBT-P, CBT-I prompted greater improvement in abnormal pain processing in patients with fibromyalgia and insomnia. Increased NREM sleep may underlie these pain processing improvements following treatment. Future research examining the potential role of NREM sleep in central sensitization and pain processing is warranted. Support: National Institute of Arthritis and Musculoskeletal and Skin Diseases (R01AR055160 and R01AR005160-S1; McCrae, PI). Data collected as part of clinical trial NCT02001077 Sleep and Pain Interventions (SPIN) at the University of Florida (McCrae, PI).